RANCANGAN PERANGKAT PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA KELAS IV SEKOLAH DASAR - Reyhani Lazza Firdaus, - (2021)
This study discusses the design of cooperative learning tools that use the Student Teams Achievement Division type to improve the social skills of students in grade IV in elementary schools. This research was conducted because it saw the low social skills of grade IV elementary school students during the learning process so that improvements needed to be made to improve these social skills by designing a learning device using a cooperative learning model type Student Teams Achievement Division. As for this study, the aim of this research is to describe the design of learning devices in which there is a Learning Implementation Plan (RPP), Learning Media, Teaching Materials, Learning Evaluation and Student Worksheets (LKPD). In this study, using a qualitative approach and the Delphi method which aims to get input and agreement from three competent experts or experts on the topic of this research, namely the design of cooperative learning devices type Student Teams Achievement Division to improve students' social skills by doing two cycles or rounds. . The object in this study is the design of learning devices. The data in this study were obtained from the results of the analysis of input and suggestions from each expert or expert on pre-designed learning designs. The results of this research are in the form of a cooperative learning device design type Student Teams Achievement Division in which there is a Learning Implementation Plan (RPP), Learning Media, Teaching Materials, Learning Evaluation and Student Worksheets (LKPD) that are agreed upon and predicted by experts or experts can improve the social skills of fourth grade elementary school students.